Mechanisms to activate artificial intelligence in the educational process- Requirements and challenges - Bellil, Affaf (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2025)
Artificial intelligence is considered the talk of the hour, especially in the educational field, as it has become a powerful tool for developing the educational process and improving its quality by contributing to improving evaluation methods and facilitating the self-learning process through smart platforms capable of interacting with learners and directing them, and To achieve the maximum benefit from artificial intelligence in education, it is necessary Activating specific mechanisms that facilitate the process of its application, and based on the descriptive approach, in this research paper we will discuss the definition of artificial intelligence and its origins We will reveal its roles in the educational process, and we will also shed light on its requirements, mechanisms, and the challenges facing its application in education.